The effect of landscape design elements and mosque design on the thermal environment of main prayer hall: a case study of Tuanku Mizan Zainal Abidin Mosque, Putrajaya - Ibrahim, Aishatus Solihah; Mohamed Shuhaimy, Nuranis Fadhilah; Abu Bakar, Aniza; Hj Mohd Ariffin, Noor Aziah; Mohd. Din, Shamzani Affendy (2012)
Climate plays a vital role in thermal comfort environment. In hot and humid climate, the increment of air temperature is normally associated with the associating phenomena of the urban heat island and green house effect. Studies have pointed out that the external features of the surroundings have a direct impact on the internal thermal environment of buildings which requires a profound perception on environmental parameters such as air temperature, relative humidity, wind speed, and solar radiation. Implementation of bioclimatic design ought to be integrated as it may have an impact on the indoor thermal environment of buildings. Thus, this research paper aims to investigate the influence of landscape surface materials and mosque design towards the indoor thermal environment of the mosque in Putrajaya, Malaysia. Several research methods have been applied such as survey questionnaire, site inventory, observation, and measuring the environmental parameters such as air temperature, wind speed, relative humidity, and solar radiation. Some of the findings show that the concrete slab material of the outdoor landscape design absorbs more heat, which the highest reading is more than 50°C, and secondly the internal spaces reading of air temperature beside the pool areais lower which is at 27°C compared to the air temperature within the main prayer hall which is at 31°C.Hence, the paper will establish that landscape design elements such as the hard surface materials do have an impact towards the indoor thermal environment of the main prayer hall.